1995
DOI: 10.1088/0029-5515/35/11/i03
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence during ergodic divertor experiments in Tore Supra

Abstract: The level of density fluctuations is shown to decrease during ergodic divertor operation in Tore Supra. This decrease of the turbulence is correlated with the onset of a temperature pedestal and a local improvement of the confinement. This pedestal is located close to the electric shear layer, i.e. within a narrow region between the plasma core and the ergodic layer. The onset of such a pedestal explains why the central electron temperature is not changed when the ergodic divertor is switched on, in spite of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
56
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(69 citation statements)
references
References 23 publications
12
56
1
Order By: Relevance
“…;e to ! ;i direction; (iii) the normalized Sk drawn in the inset is flattened during DED, indicating a broadening of the k spectrum and thus a reduction of turbulence correlation length; (iv) the strong reduction of Sk at small k reveals the suppression of large structure turbulence by DED, as observed earlier [5]. The influence of DED on turbulent eddies can be further seen from the radial (poloidal) correlation length, l cr l c , which is defined as the inverse of the k r k spectrum width detected by two radially (poloidally) separated probes [12].…”
supporting
confidence: 62%
See 3 more Smart Citations
“…;e to ! ;i direction; (iii) the normalized Sk drawn in the inset is flattened during DED, indicating a broadening of the k spectrum and thus a reduction of turbulence correlation length; (iv) the strong reduction of Sk at small k reveals the suppression of large structure turbulence by DED, as observed earlier [5]. The influence of DED on turbulent eddies can be further seen from the radial (poloidal) correlation length, l cr l c , which is defined as the inverse of the k r k spectrum width detected by two radially (poloidally) separated probes [12].…”
supporting
confidence: 62%
“…Meanwhile, the local effects of the magnetic ergodization on edge turbulence and turbulent cross-field transport have also been studied both experimentally [1,5,6] and theoretically [7,8]. It has been observed on TEXT [1] and Tore Supra [2,5,6] that in the ergodic divertor (ED) configuration the edge density fluctuations are decreased whereas the turbulent cross-field diffusivity is less affected. However, a systematic investigation of the turbulence properties, such as frequency and wave-number spectra and the fluctuation propagations, has not been made or was done for a reduced set of wavenumber values [5].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In simulation [13], it is shown that before RMP the modes with k // ≈ 0 on rational surfaces are subject to strong instabilities whereas during RMP the modes are damped by resistivity because k // becomes finite and nonzero. With RMP, the experimental measurements [10,15] also showed a strong reduction of the large-scale turbulence structures in the ergodic zone. Consequently, the blob size, based on large turbulence structures, is reduced by the RMP when the blobs generate and pass radially through the ergodic layer.…”
Section: Resultsmentioning
confidence: 99%